New Perspectives on Imagology - Zocco, Gianna (Brill, 2022)
With this volume, the editors Katharina Edtstadler, Sandra Folie, and Gianna Zocco propose an extension of the traditional conception of imagology as a theory and method for studying the cultural construction and literary representation of national, usually European characters. Consisting of an instructive introduction and 21 articles, the book relates this sub-field of comparative literature to contemporary political developments and enriches it with new interdisciplinary, transnational, intersectional, and intermedial perspectives. The contributions offer [1] a reconsideration and update of the field's methods, genres, and theoretical frames; [2] trans-/post-national, migratory, and marginalized perspectives beyond the European nation-state; [3] insights into geopolitical dichotomies such as Orient/Occident; [4] intersectional approaches considering the entanglements of national images with notions of age, class, gender, sexuality, and ethnicity/race; [5] investigations of the role of national images in visual narratives and music.